RESPONSE AND TOLERABILITY OF SOFOSBUVIR PLUS DACLATASVIR IN ELDERLY PATIENTS WITH CHRONIC HEPATITIS-C - Ahmad, Mahmood; Mahmud, Yasir; Irfan, Muhammad; Nadeem, Muhammad Arif; Mohsin, Aftab (Journal of Ayub Medical College Abbottabad, 2019)
Background: The approval of direct acting anti-viral drugs has expanded the treatment access to all patient populations including elderly patients, who were previously neglected. We evaluated the response & tolerability of sofosbuvir plus daclatasvir in old age patients > 60 year infected with HCV. Methods: In this prospective observational study, 100 patients were enrolled and were divided into two groups: aged 60-69 (group A) and aged 70 and older (group B). All the patients were given sofosbuvir plus daclatasvir. Sustained virologic response at 12 weeks was the primary endpoint. Response and tolerability of treatment were analysed and compared between these patient groups. Results: Hundred patients aged ‰¥60 years were treated with sofosbuvir plus daclatasvir. Sustained virologic response rate was 91% in group A (aged 60- 69 year) and 87.8% in group B (aged 70 year and older). No significant adverse effect was noted in both groups. No treatment discontinuation was encountered. Conclusions: Direct acting antiviral drug therapy is highly efficacious and safe for the treatment of HCV in older adults. Keywords: Chronic hepatitis C; Sofosbuvir; Daclatasvir; Cirrhosis; Sustained virological response; Elderly patients